2014
DOI: 10.1155/2014/178274
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Acid Stress Response in DifferentSaccharomycesStrains

Abstract: Yeast cells need to respond to a variety of stresses found in such different conditions as gastrointestinal tract after probiotic ingestion or fermentation vat during ethanol production. In the present study, H+ neutralisation capacity, membrane fatty acid composition, H+-ATPase activity, and cytosolic Ca2+ concentration were evaluated in yeast cells used for probiotic (Saccharomyces boulardii) and laboratory (Saccharomyces cerevisiae W303) purposes, as well as in some W303 mutant strains for ENA1 gene and S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…These orthologous proteins have been associated with various physiological functions. ScCrz1p participates in the acidic and alkaline pH response through regulation of intracellular Ca 2ϩ (21,22) and, in Na ϩ /Li ϩ hypertonic saline stress, by increasing the activity of the Na ϩ /Li ϩ -ATPase proton pump (19). Overexpression of ScCrz1p was shown to increase the fermentative capacity of industrial strains (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These orthologous proteins have been associated with various physiological functions. ScCrz1p participates in the acidic and alkaline pH response through regulation of intracellular Ca 2ϩ (21,22) and, in Na ϩ /Li ϩ hypertonic saline stress, by increasing the activity of the Na ϩ /Li ϩ -ATPase proton pump (19). Overexpression of ScCrz1p was shown to increase the fermentative capacity of industrial strains (38).…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae, Crz1p (ScCrz1p) is involved in metal ion resistance (19), cell wall biogenesis (20), regulation of the transcriptional response to alkaline pH (21) or acid stress (22), and tolerance to ethanol (23). In Candida albicans, Crz1p (CaCrz1p) is implicated in antifungal susceptibility (24), virulence, lithium ion resistance, filamentation, and the regulation of pH homeostasis under alkaline and acidic conditions (24,25).…”
mentioning
confidence: 99%
“…Fungal resistance or adaptation to weak organic acids rely on several mechanisms. In S. cerevisiae and other fungi, it includes maintenance of the cell wall structure, changes in plasma membrane or cell wall composition, metal metabolism, and activation of ATP-consuming membrane transporters to remove protons and anions [ 126 ]. Ullah et al [ 127 ] showed that S. cerevisiae adaptation to sorbic or acetic acid resulted in a decreased diffusional entry of the molecule.…”
Section: Prevention and Control Of Fungal Spoilage In Dairy Producmentioning
confidence: 99%
“…At the end of fermentation, the pH of the culture had dropped to 3.8, indicating a highly acidic culture environment due to the presence of acetic acid (~3 g/L). A low pH environment is known to cause acid stress in yeasts, resulting in reduced membrane permeability, anion extrusion, and alters expression of genes that are key for yeast growth [29,30].…”
Section: Batch Bioreactor Fermentations Using Semi-defined Mediamentioning
confidence: 99%